A serious game for the responsible use of fossil fuel-powered vehicles. (6th October 2022) - Arboleda, Francisco Javier Moreno; Romero, Javier Esteban Parra; Szczęsna, Agnieszka
Serious gaming has gained increasing prominence in climate change communication, and provides an opportunity to engage people in topics related to environmental protection. This paper presents the design and evaluation of a serious game that concerns pollution generated by fossil fuel-powered vehicles. Serious games might be an effective and motivational tool in that field. The game's intention is to motivate the participants to change towards sustainable lifestyles. To achieve this goal, an enhanced game design methodology was proposed and a serious mini-game prototype was developed.